Figurative Structuring Systems in the Optical Art: ندى عايد يوسف (Al-Academy, 2016)
Through the history of art movements, abstraction has been rotating between appearance and disappearance, mounting and stillness while its performances differed between reduction and simplification on the one hand and between the use of chromatographic and linear abstraction on the other. As a result, to what is mentioned, abstraction has appeared in many different artistic forms underlying the systematicity of the plastic art history.However, according to a contemporary point of view that comes up with the scientific revolution, the art of optical deceiving (illusion) appeared to find a hybrid art form that locates between the geometricity of abstraction and the scientific, visual and psychological foundations that are linked with the intellectual transformations.Consequently, modern strategies and styles appeared. Those are involved in relations with the eye physiology and mind perceptions and those contribute creating figurative changes in the map of the optical formation that by turn leads to a multiplicity of readings. Therefore, this research, ' The Figurative Structuring Systems in the Optical Art', studies the figurative systems, their relations and their founding references.This paper includes four chapters. The first chapter deals with the problem of the research and its aim that is all about uncovering the figurative structuring systems in the visual art relying on some related art works.Chapter two includes four sections deal with defining the concept of the optical art along with stating the founding references of the figurative system via studying the mathematical, physiological and physical systems. Chapter three, however, includes the analysis of the samples while the fourth chapter deals with the most important results that have been reached